Environmental and Gender Impacts of Land Tenure Regularization in Africa : Pilot Evidence from Rwanda - Ali, Daniel Ayalew (World Bank, Washington, DC, 2016)
Although recent developments have increased interest in African land tenure, Rwanda's nation-wide Land Tenure Regularization (LTR) program is one of a few models to address these issues at the required scale. An impact evaluation of this program highlights four main effects; namely, 1) significant and large investment impacts that are particularly pronounced for women; 2) improved land access for legally married women and better recordation of inheritance rights; 3) a reduction in the probability of having documented land ownership for legally unmarried women; and 4) a reduction in land market activity rather than distress sales. A primary reason for the Government of Rwanda to initiate LTR was to increase levels of land tenure security. LTR also demonstrated a major impact on inheritance related knowledge and awareness. Authors found a significant increase in the likelihood that landholders in the program areas would now know who would inherit their parcel.